Kepemimpinan Organisasi Masa Depan Konsep dan Strategi Keefektifan - Nursya’bani Purnama (Jurnal Siasat Bisnis, 2005)
Future organization will face business environment changes that demand organization to build new competence. Leadership becomes a critical factor that must be possessed by future organization leaders. To sustain organization’s success, future organization leaders have to formulate the precise and clear vision and communicate the vision through all organization elements. The prominent competence possessed by future orga¬nization leaders involves strategic thinking ability, leadership in change and skill developing a good relationship.In addition to there are special skills concering difficult learning, maximing energy, resonant simplicity, multiple focus, and mastering inner sense. Key words: Kepemimpinan, Kompetensi, Strategi Keefektifan